Types of Rats and Their Parasites That Potential to Transmit Disease in Tugu District, Semarang City - Ning Setiati; Rusyda Auliya; Partaya Partaya; F. Putut Martin Herry Bodijantoro; Dyah Rini Indriyanti; Priyantini Widiyaningrum (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Rats are known as vectors and reservoirs for various types of ecto and endoparasites. The existence of rats as cosmopolitan animals allows for complex parasitic transmission due to the relationship between humans, animals, and the environment. This study aimed to provide informative data on the types of rat along with their ecto- and endoparasites. This research is a qualitative descriptive study. Data collection was carried out by random sampling survey with a point time approach. Data collection was carried out in 4 villages, namely Tugurejo, Mangkang Wetan, Mangunharjo, and Mangkang Kulon Villages, Tugu District, Semarang City. A total of 89 rats were obtained, the species obtained were R. norvegicus, R. argentiventer, R. exulans, R. tiomanicus, R. surifer, R. tanezumi, B indica, and S. murinus. Ectoparasite infestation was found in all types of rats except S. murinus. The ectoparasites found were Xenopsylla cheopis and Laelaps echidninus which were reported as the main vectors of murine typhus, epidemic typhus, bartonellosis as well as scrub typhus and Q-fever disease. Endoparasite infestation was found in the intestinal organs, namely Diphyllobothrium sp. and two species of worm eggs Hymnoepis sp. and Trichuris trichiura which were reported as the cause of Diphyllobothriasis as well as digestion, absorption, which can result in the loss of protein, carbohydrates, fats, and blood in large quantities. Diphyllobothriasis is not transmitted from person to person, more than one family member can be infected by sharing common meals and having similar eating habits. This study can be used as an early warning for community against the potential of infectious diseases from rats as vectors in Tugu District, Semarang related to rats density, endoparasites and their ectoparasites.